Assessing awareness of long-term health risks among women with a history of preeclampsia: a cross-sectional study - Mpalatsouka, Ismini; Zachariou, Myria; Kyprianidou, Maria; Fakonti, Georgia; Giannakou, Konstantinos (Frontiers in Medicine, 2023)
Pregnancy complications, such as hypertensive disorders, present a substantial global public health challenge, with significant long-term implications for maternal and offspring health. This cross-sectional study aims to determine the level of awareness regarding long-term health risks among women who experienced preeclampsia during pregnancy in Cyprus and Greece. The study participants included adult women with a history of preeclampsia, while women with normal pregnancies were used as the comparison group. Data collection took place between June 2021 and February 2022, utilizing an online, self-administered questionnaire. The study included 355 women, with 139 (39.2%) in the preeclampsia group and 216 (60.8%) in the comparison group. Findings revealed that more than half of the women with prior preeclampsia (55.4%) were not aware of hypertensive disorders that can occur during pregnancy before their diagnosis, and a similar percentage (45.2%) had not received information about the long-term health risks following their diagnosis. Remarkably, only 3 participants (4.7%) with a history of preeclampsia were aware of the risk of developing cardiovascular diseases. There were no statistically significant differences between the preeclampsia and the comparison group regarding their concerns about long-term health risks, frequency of health checks, perceptions of factors influencing cardiovascular disease development, and doctor communication about different health topics, except from hypertension or high blood pressure. The study underscores the low level of awareness of long-term health risks among women with prior preeclampsia in Cyprus and Greece. This emphasizes the importance of implementing public health programs aimed at promoting cardiovascular risk assessment and effective management, both for clinicians and women with have experienced preeclampsia.